Coupled Assessment of Fire Behavior and Firebrand Dynamics - Thomas, Jan C.; Mueller, Eric V.; Gallagher, Michael R.; Clark, Kenneth L.; Skowronski, Nicholas; Simeoni, Albert; Hadden, Rory M. (Frontiers in Mechanical Engineering, 2021)
The hazards associated with firebrands have been well documented. However, there exist few studies that allow the hazard from a given fire to be quantified. To develop predictive tools to evaluate this hazard, it is necessary to understand the conditions that govern firebrand generation and those that affect firebrand deposition. A method is presented that allows time resolved measurements of fire behaviour to be related to the dynamics of firebrand deposition. Firebrand dynamics are recorded in three fires undertaken in two different ecosystems. Fire intensity is shown to drive firebrand generation and firebrand deposition flux – higher global fire intensities resulting in the deposition of more, larger firebrands at a given distance from the fire front. Local firebrand dynamics are also shown to dominate the temporal firebrand deposition with periods of high fire intensity within a fire resulting in firebrand shower at deposition sites at times commensurate with firebrand transport. For the range of fire intensities studied, firebrand deposition can be expected up to 200 m ahead of the fire line.